Novel high-performance microstrip diplexer for 5G mid-band and wide-band applications: Design, analysis and manufacturing - Salah I. Yahya; Farid Zubir; Mohammed Abdel Hafez; Leila Nouri; Muhammad Akmal Chaudhary; Maher Assaad; Abbas Rezaei; Noorlindawaty Md Jizat (PLoS ONE, 2025)
This paper presents the design and experimental results of a microstrip diplexer with a high performance for 5G applications. The introduced diplexer has compact size, novel structure, low losses, and wide fractional bandwidth. Notably, it exhibits a novel microstrip layout with a very compact size of 0.004 λg2. The resonance frequencies are tuned at 1.1 GHz and 3.2 GHz for mid-band 5G applications. The presented structure has the fractional bandwidths (57.3%, 44.6%) and insertion losses (0.07 dB, 0.04 dB). Additionally, it features two flat channels with two low maximum group delays of 0.86 ns, 0.4 ns in the 1st and 2nd passbands, respectively. A perfect mathematical design method is applied to find the behavior of the introduced resonator, as well as the most effective physical dimensions. For improving the performance and miniaturization, an optimization method is used. To validate the design approach, the proposed diplexer is fabricated and then measured, demonstrating a close agreement between the simulation and measurement results. This highlights the effectiveness of our design approach and underscores the potential of the proposed diplexer for enabling efficient and reliable communication in the rapidly evolving field of telecommunications.